Comparison of Farfan modified and Frobin methods to evaluate the intervertebral disc height - Kanas,Michel (2014)
OBJECTIVE: To evaluate the reliability and reproducibility of Farfan modified and Frobin methods to measure the intervertebral disc height in radiographs with inter- and intraobserver comparison. METHOD: Six radiographs of different patients treated for low back pain have been collected and digitized, and five lumbar disc of each patient were evaluated by six examiners with different levels of experience. The measures were done in Image Pro Plus 6.0 software. RESULTS: When compared, both methods showed more than 95% concordance. In intraexaminer analysis, both also shown to be reliable and reproducible, with a high level of concordance. By comparing the correlation between classes of examiners, the higher the level of experience, the greater the agreement for both methods. CONCLUSION: Farfan modified and Frobin are reliable methods to measure the disc height in the lateral radiographs. The higher level of experience of the examiner, the higher was the correlation between measurements.